Effects of Eucalypt ashes from moderate and high severity wildfires on the skin microbiome of the Iberian frog (Rana iberica). (15th November 2022) - Coelho, Laura; Afonso, Mariana; Jesus, Fátima; Campos, Isabel; Abrantes, Nelson; Gonçalves, Fernando J.M.; Serpa, Dalila; Marques, Sérgio M.
Abstract: Forest fires can threaten amphibians because ash-associated contaminants transported by post-fire runoff impact both terrestrial and aquatic ecosystems. Still, the effects of these contaminants on the skin microbiome of amphibians have been overlooked. Thus, the main objective of this study was to assess the effects of ash from different severity wildfires (moderate and high) on the skin microbiome of the Iberian frog ( Rana iberica ). Bacterial isolates sampled from R. iberica skin microbiome were tested for their antimicrobial activity against the pathogen Aeromonas salmonicida . The isolates with antimicrobial activity were identified and further exposed to several concentrations (0, 6.25, 12.5, 25, 50, 75, and 100%) of Eucalypt ( Eucalyptus globulus ) aqueous extracts (AAEs) of ash from both a moderate and a high severity wildfire. The results showed that 53% of the bacterial isolates presented antimicrobial activity, with Pseudomonas being the most common genus. Exposure to AAEs had diverse effects on bacterial growth since a decrease, an increase or no effects on growth were observed. For both ash types, increasing AAEs concentrations led to an increase in the number of bacteria whose growth was negatively affected. Ash from the high severity fire showed more adverse effects on bacterial growth than those from moderate severity, likely due to the higher metal concentrations of the former. This study revealed that bacteria living in Iberian frogs' skin could be impaired by ash-related contaminants, potentially weakening the individual's immune system. Given the foreseen increase in wildfires' frequency and severity under climate change, this work raises awareness of the risks faced by amphibian communities in fire-prone regions, emphasising the importance of a rapid implementation of post-fire emergency measures for the preservation and conservation of this group of animals. Graphical abstract: Image 1 Highlights: The toxicity of wildfire ashes to skin bacteria of Rana iberica was assessed. Bacterial isolates from Rana iberica 's skin showed antimicrobial activity. Ashes from the high severity fire were more toxic than the moderate severity one. Metals were likely the main ash-contaminants affecting bacteria growth. Ash contamination might influence Rana iberica 's skin microbiome.